THE ROLE AND TASKS OF EDUCATION IN THE DEVELOPMENT OF SOCIETY - Omonboyeva Saltanat (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Nowadays, the significance of education as an act or mechanism of societal innovation and evolution is universally acknowledged. This paper opens the idea of social change. Education has already been recognized as a main form of social action, with educators and curriculum businesses serving as social agents. By remodeling people's views and perceptions to the typical approach, training can assist through growing a safer, brighter, and a lot greater prosperous world and hence promote sustainability. While we take any action, we need to first identify and apprehend the motive and responsibility of education. As a result, this will be crucial for human growth in the direction of turning into profitable and responsible citizen.